2005
DOI: 10.1002/chin.200515145
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of 5‐Substituted Amino‐2,4‐diamino‐8‐chloropyrimido‐[4,5‐b]quinolines (IX) as Novel Antimalarials.

Abstract: Fused pyrimidine derivatives R 0515 Design, Synthesis and Evaluation of 5-Substituted Amino-2,4-diamino--8-chloropyrimido-[4,5-b]quinolines (IX) as Novel Antimalarials. -(JOSHI, A. A.; NARKHEDE, S. S.; VISWANATHAN*, C. L.; Bioorg. Med. Chem. Lett. 15 (2005) 1, 73-76; Dep. Pharm. Chem., Bombay Coll. Pharm., Bombay 400 098, India; Eng.) -R. Langenstrassen 15-145

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The compounds were synthesized and evaluated by Rane's test for blood schizontocidal activity in mice infected by P. berghei [129]. The compounds with bulky substitution on 9-anilino ring (93), and trisubstituted 9-anilino ring [ Becker et al reported a series of potent inhibitors of P. falciparum thioredoxin reductase (PfTrxR), which reduces thioredoxin (Trx) via a CysXXXXCys pair, located penultimate to the C-terminus Gly [133].…”
Section: Ring-modified Quinolines (Figs 15e17)mentioning
confidence: 99%
“…The compounds were synthesized and evaluated by Rane's test for blood schizontocidal activity in mice infected by P. berghei [129]. The compounds with bulky substitution on 9-anilino ring (93), and trisubstituted 9-anilino ring [ Becker et al reported a series of potent inhibitors of P. falciparum thioredoxin reductase (PfTrxR), which reduces thioredoxin (Trx) via a CysXXXXCys pair, located penultimate to the C-terminus Gly [133].…”
Section: Ring-modified Quinolines (Figs 15e17)mentioning
confidence: 99%
“…However, the nature and size of the substituents present at the 5-amino function in the pyrimidoquinoline nucleus significantly determine the antimalarial activity. [59] Apart from this, pyrimido-quinolines also exhibit other important biological properties like antimicrobial, [60] anticancer, [61] and anti-inflammatory activities. [62]…”
Section: Quinolinesmentioning
confidence: 99%
“…16 For example, Viswanathan and co-workers reported a synthesis by sodium alkoxide promoted cyclization of guanidine nitrate with malononitrile in dry ethanol or methanol (Scheme 1). 7 Soon afterwards, Jarvo and co-workers described a methodology for the synthesis of 4,6-diaminopyrimidines via the same reaction from 2-substituted malononitriles using potassium tert-butoxide as base. 17 A similar synthetic strategy also was reported by the Kobarfard group via the reaction of thiourea and malononitrile in absolute ethanol as solvent.…”
Section: Figure 1 Pyrimidine Motif In Marketed Pharmaceuticalsmentioning
confidence: 99%
“…Recently, various special substitution types and specific biological activities of pyrimidine derivatives were reported; among the family of pyrimidines, the 4,6-diaminopyrimidines have been found to show diverse biological activities, such as anti-dengue and anti-HCV, 2 antimicrobial, 3 antiplatelet aggregation, 4 antitumor, 5 antiviral, 6 antimalarial, 7 potent dual M3 antagonistic and PDE4 inhibitory, 8 troponin I-interacting kinase (TNNI3K) inhibitory, 9 and Janus kinase 3 inhibitory 10 activity.…”
Section: Figure 1 Pyrimidine Motif In Marketed Pharmaceuticalsmentioning
confidence: 99%